CDC’s Global Disease Detection Program and the international health regulations: providing early warning to CDC for human rabies outbreaks (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Texto em inglêsIn 2003, the spread of SARS alerted public health leaders that novel pathogens could be transmitted along international travel routes with unprecedented speed. With the realization that an outbreak anywhere in the world was a potential threat to virtually all countries, the United States Congress in 2004 authorized the appropriation of funds to establish a Global Disease Detection (GDD) program, based at the CDC, with the aim of promptly detecting and mitigating the consequences of emerging threats. The GDD program provides a platform to develop and strengthen global capacity to rapidly detect, identify, and contain emerging infectious disease and bioterrorist threats in line with the International Health Regulations (IHR), which entered into force in June 2007 and legally requires all signatory nations to establish systems to detect and respond to new disease threats. The GDD program was subsequently selected by WHO as a key partner to help implement the IHR (2005) for its 194 member states and in 2009 was designated a WHO Collaborating Center for Implementation of IHR National Surveillance and Response Capacity. A significant component of GDD is the GDD Operations Center (GDDOC), an epidemic intelligence unit which uses novel, event‐based surveillance techniques to provide CDC programs with a single source of reliable, comprehensive, and high quality information on international disease outbreaks, and provides logistical and financial support to CDC programs for emergency deployments to international outbreaks. Technological advances have revolutionized the way information is accessed, and event-based surveillance provides a mechanism for the organized and rapid collection and verification of information about events that are a risk to public health, particularly with regard to emerging zoonoses, which countries sometimes cannot or do not report to the global public health community. A re-emerging, global zoonosis that the GDDOC actively monitors is rabies in both animals and humans. Since 2009, the GDDOC has supported provided epidemiologic, logistical, or financial support to CDC’s Rabies Program for emergency deployments to the Dominican Republic, Peru, Ecuador, and Kenya to mitigate outbreaks of human rabies associated with canine and vampire bat rabies. Because of the GDDOC’s work to actively identify and report rabies-related event-based surveillance data to CDC’s Rabies Program, CDC is better positioned to respond to a request for technical assistance by the affected country and establish core capacities in compliance with IHR.